Ontology and Function of Fibroblast-Like and Macrophage-Like Synoviocytes: How Do They Talk to Each Other and Can They Be Targeted for Rheumatoid Arthritis Therapy? - Tu, Jiajie; Hong, Wenming; Zhang, Pengying; Wang, Xinming; Körner, Heinrich; Wei, Wei (Frontiers in Immunology, 2018)
Fibroblast-like synoviocytes (FLS) and macrophage-like synoviocytes (MLS) are the two main cellular components of the synovium. It has been widely reported that FLS and MLS play essential roles in the joint pathology of rheumatoid arthritis (RA). Although various studies have analysed both human and animal tissues and have shown that both cell types are involved in different stages of RA, ontology and specific functions of both cell populations and their interactions are not well understood. In this review, we will summarize recent research on FLS and MLS in RA and focus on the development and function of two predominant synovial cell types. In addition, we will discuss the communication between FLS or MLS and highlight potential treatments for RA that involve synoviocytes.